Head-to-Head Comparison of 68Ga-PSMA-11 PET/CT and Multiparametric MRI for Pelvic Lymph Node Staging Prior to Radical Prostatectomy in Patients With Intermediate to High-Risk Prostate Cancer: A Meta-Analysis - Wang, Xueju; Wen, Qiang; Zhang, Haishan; Ji, Bin (Frontiers in Oncology, 2021)
Purpose To compare the diagnostic performance of 68Ga-PSMA-11 PET/CT and mpMRI for pelvic lymph node staging prior to radical prostatectomy in prostate cancer (PCa) patients based on per patient data. Methods PubMed and Embase databases were searched until October 2020 for eligible studies evaluating head-to-head comparison of 68Ga-PSMA-PET/CT and mpMRI for the detection of pelvic lymph node metastases (PLNMs) using pelvic lymph node dissection (PLND) as gold standard. The pooled sensitivity, specificity, and area under the summary receiver-operating characteristics curve (AUC) were determined for the two imaging modalities. Results Nine studies with 640 patients were included. The pooled sensitivity, specificity, and AUC for 68Ga-PSMA-11 PET/CT vs. mpMRI were 0.71 (95% CI: 0.48–0.86) vs. 0.40 (95% CI: 0.16–0.71), 0.92 (95% CI: 0.88–0.95) vs. 0.92 (95% CI: 0.80–0.97), and 0.92 (95% CI: 0.88–0.95) vs. 0.82 (95% CI: 0.79–0.86), respectively. There was substantial heterogeneity for both imaging modalities, and meta-regression analysis revealed that the number of patients, prevalence of PLNMs, PSA level, reference standard, and risk classification might be the potential causes of heterogeneity. Conclusion This meta-analysis of head-to-head comparison studies confirms that there is a trend toward a higher sensitivity and diagnostic accuracy of 68Ga-PSMA-11 PET/CT compared to mpMRI for the detection of PLNMs in PCa patients. Nevertheless, according to current guidelines, PLND still needs to be recommended in case of negative results from 68Ga-PSMA-11 PET/CT due to significant risk of malignancy.